2011
DOI: 10.1039/c1dt11565k
|View full text |Cite
|
Sign up to set email alerts
|

New stable aryl-substituted acyclic imino-N-heterocyclic carbene: synthesis, characterisation and coordination to early transition metals

Abstract: The synthesis of the bulky 1-(1-arylimino-2,2-dimethylpropyl)-3-(aryl)imidazolium salt from the corresponding imidazole and the activated imidoyl chloride is presented. The absence of acidic protons adjacent to the iminic carbon allowed for the first isolation of an imino-N-heterocyclic carbene of this ligand class. The free carbene was isolated, structurally characterised, and coordinated to titanium, zirconium, hafnium and chromium. The resulting metal halide complexes were fully characterised and were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 70 publications
11
44
0
Order By: Relevance
“…A decrease in the C]N stretching frequency from 1662 cm À1 for the free ligand to 1609 cm À1 for 1 suggests coordination of the ligand to the metal centre in a bidentate mode through both the carbenoid carbon and the imine nitrogen atoms. A comparable decrease in stretching frequency was also observed in TiCl 4 (C^Imine) and other related early transition metal complexes [12].…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…A decrease in the C]N stretching frequency from 1662 cm À1 for the free ligand to 1609 cm À1 for 1 suggests coordination of the ligand to the metal centre in a bidentate mode through both the carbenoid carbon and the imine nitrogen atoms. A comparable decrease in stretching frequency was also observed in TiCl 4 (C^Imine) and other related early transition metal complexes [12].…”
Section: Resultssupporting
confidence: 55%
“…The catalytic activities of these new complexes towards ethylene polymerisation were assessed. TiCl 4 (C^Imine) showed promising activities and thereby warranted further tailoring of the steric and electronic parameters of the complex through ligand variations [12]. We herein report the synthesis and isolation of the corresponding titanium aryloxo complexes and the attempted synthesis of titanium imido complexes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Both complexes are not particularly active towards ethylene polymerization (in toluene at atmospheric pressure and room temperature in the presence of 1000 equivalents methylaluminoxane (MAO) as cocatalyst)[183]. 16 Cr complexes with acyclic imino NHC ligands[183] In2012, Braunstein et al reported the Cr complexes containing the anionic NHC amidinato ligands (Cr-86 and Cr-87, Figure 4.17) [184]. The ligand is bidentate through NHC and amidine nitrogen donation.…”
mentioning
confidence: 99%
“…15 Cr(III) complexes bearing C^S and C^S^C types of hybrid NHC ligands[180] In 2011, Lavoie et al[183] reported the synthesis of complexes containing aryl-substituted acyclic imino NHC ligand (Cr-84 and Cr-85,Figure 4.16) from the reaction of CrCl 2 (THF) -imidazol-2-ylidene carbene[183]. Cr-85 has a highly distorted octahedral geometry with Cr-C carbene bond length of 2.041(4) Å.…”
mentioning
confidence: 99%